Chaotic oscillation generator - V. V. Fedyanin; V. K. Fedorov; I. E. Pestrikova (Омский научный вестник)
The article analyzes existing schemes of chaos generators. Numerical and simulation modeling is carried out aimed at identifying chaotic dynamics. Based on wellknown concepts, a chaos generator is developed and a simulation model is built. A mathematical description of the generator is given and phase portraits are obtained. Diagrams of chaotic oscillations of the Lorentz model and the Colpitts model are presented. The operation of the Van der Pol generator is considered and the chaotic processes that arise during external harmonic oscillations are shown. Chua's model is presented, its mathematical description is given, and an analysis of oscillations in the deterministic chaos regime is presented.